Breaking the Chains of Tuberculosis: Quantifying the Effects of Literacy, Population Density, and Access to Improve Sanitation to Support Defense Health and Security in Indonesia - Reinpal Falefi; Hikmat Zakky Almubaraq; Nora Lelyana; Makmur Supriyatno (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2023)
Background: Tuberculosis (TB) is a global health problem. It poses a significant burden worldwide, requiring urgent control measures and research for effective reduction especially in Indonesia.Objective: Investigating the effects of literacy, population density, and access to improved sanitation on TB incidence can provide insights into the relationship between these factors.Methods: This study was conducted in Jakarta, Indonesia from June to July 2023, using secondary data from 2005 to 2021. It employed a quantitative cross-sectional design to examine the relationship between variables. Data were collected from the ASEAN database and analyzed using descriptive and path analysis techniques to determine variable effects and significance. The study found that the incidence of tuberculosis in Indonesia initially decreased from 2005 to 2020 but significantly increased in 2021.Results: Population density, adult literacy rate, and access to improved sanitation all showed positive trends. Significant direct effects were observed among most variables, and indirect effects of population density on tuberculosis incidence were also identified through literacy and sanitation. The final model showed that higher population density correlated with increased access to sanitation and literacy rate, while access to improved sanitation was associated with reduced tuberculosis incidence. Overall, the model had a very good fit based on the indicators.Conclusion: Priority investments in sanitation infrastructure, especially in densely populated areas, along with improved access to sanitation facilities, combined with targeted health education campaigns and collaboration across defense, health, and education sectors, are recommended to enhance tuberculosis prevention and control